Cerebrospinal fluid pressure in pyogenic meningitis. Issue 6 (June 1989) - Minns, R A; Engleman, H M; Stirling, H
Abstract : The pressure of cerebrospinal fluid taken at lumbar puncture was recorded objectively by strain gauge pressure measurement in 35 infants and children with pyogenic meningitis. Raised pressures were found in 33 children. The median pressure was 15 mm Hg (range 4-70 mm Hg) in all age groups. The pressure level varied throughout the infection, but a higher median pressure (19 mm Hg) was found when this was measured on the day of admission. The clinical features of the meningitis in these patients suggest that many of the presenting symptoms and signs are those of pressure. These results show that high pressure is frequently present in childhood meningitis, not just in those who die from cones or who have radiological evidence of hydrocephalus. We conclude that raised cerebrospinal fluid pressure is a frequent accompaniment of childhood meningitis and may need treatment in its own right and is therefore one further important factor influencing the course and outcome of childhood meningitis.